Efeito do tratamento com as drogas antipsicóticas haloperidol e clozapina sobre a infecção de toxoplasma gondii em cultura de células retinianas embrionárias - Silva, Valéria Palheta da (2012)
T. gondii is an obligate intracellular protozoan and the main cause of retinochoroiditis in humans. The aim of this study was to evaluate the effect of the antipsychotic drugs haloperidol and clozapine on the course of infection by T. gondii of cultured embryonic retinal cells. Embryo retinas of Gallus gallus domesticus (E12) were used for the preparation of mixed monolayer cultures of retinal cells. Cultures were maintained on plates of 96 and 24 wells by 37°C in DMEM medium supplemented with 5% fetal bovine serum for 2 days. After this period, cultures were simultaneously infected with tachyzoites of T. gondii and treated with the antipsychotics haloperidol and clozapine for 48 hours. Treatment effects were determined by both assessing cell viability with the MTT method and evaluating infection outcomes in slides stained with Giemsa. The treatment with haloperidol and clozapine cells infected with T. gondii resulted in higher viability of these cells, suggesting a possible prevention of neuronal degeneration induced by T. gondii. Additionally, intracellular replication of this protozoan in cells treated with haloperidol and clozapine were significantly reduced, possibly by modulation of the parasite s intracellular calcium concentration